1992
DOI: 10.1111/j.1476-5381.1992.tb09058.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a novel aquaretic agent, OPC‐31260, as an orally effective, nonpeptide vasopressin V2 receptor antagonist

Abstract: 1 OPC-31260, a benzazepine derivative, has been studied for its ability to antagonize the binding of arginine vasopressin (AVP) to receptors in rat liver (V1) and kidney (V2) plasma membranes, for antagonism of the antidiuretic action of AVP in alcohol-anaesthetized rats and for diuretic action in conscious normal rats. 2 OPC-31260 caused a competitive displacement of [3H]-AVP binding to both V1 and V2 receptors with IC50 values of 1.2 + 0.2 x 106M and 1.4 + 0.2 x 10-8M, respectively. 3 OPC-31260 at doses of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
155
2
5

Year Published

1992
1992
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 327 publications
(166 citation statements)
references
References 13 publications
4
155
2
5
Order By: Relevance
“…119 The feasibility of the second option (i.e., to block the V 2 receptor) has been demonstrated by several compounds that promote aquaresis in experimental animals. [120][121][122][123] The third therapeutical strategy is represented by demeclocycline, which was the first inhibitor of the renal effect of VP used in humans. This tetracycline acts by interfering with the generation and action of cAMP in the cortical and medullary collecting ducts.…”
Section: Aquaretic Drugsmentioning
confidence: 99%
“…119 The feasibility of the second option (i.e., to block the V 2 receptor) has been demonstrated by several compounds that promote aquaresis in experimental animals. [120][121][122][123] The third therapeutical strategy is represented by demeclocycline, which was the first inhibitor of the renal effect of VP used in humans. This tetracycline acts by interfering with the generation and action of cAMP in the cortical and medullary collecting ducts.…”
Section: Aquaretic Drugsmentioning
confidence: 99%
“…2A). The ICs~ of OPC-21268 for the displacement of specific AVP binding is reported to be 4x 10 -~ M and >10 -~ M for VI and V2 receptors, respectively [18], and the 1C~, of OPC-31260 for the displacement of specific AVP binding is reported to be 1.2 x 10 ~' M and 1.4 x 10 s M for VI and V2 receptors, respectively [19]. Thus.…”
Section: A Vp Activates Map Kinases Through V1 Receptormentioning
confidence: 96%
“…In experiments in vivo, it acted as a specific antagonist of the VP-induced pressor re sponse in pithed rats and conscious rats (4). More re cently, it was reported that OPC-31260 selectively antagonized binding to the V2-subtype of the VP recep tor in a competetive manner (5).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, nonpeptide V1 and V2-receptor antago nists were developed, i.e., OPC-21268 and OPC-31260, respectively (4,5). OPC-21268 selectively antagonized binding to the V1-subtype of the VP-receptor in a com petitive manner (4).…”
Section: Introductionmentioning
confidence: 99%